Value Relevance of Accounting Information for Chinese High-technology Industry - Luo, xiaojing (2016)
This paper seeks to investigate the value relevance of accounting information for Chinese high-technology industry and make a comparison by incorporating all other industries. Return model and price model are used to examine the association between the financial variables and market adjusted return or stock price. And we use fixed effect model as robustness check for the regression results from OLS model. Results show that accounting information such as earnings, book value of equity, selling and administration expense, depreciation and amortization expense of high-technology industry are strongly associated with price ratio, therefore, are value relevant. However, almost all the coefficients of level and change in earnings and cash flow from operation to market adjusted return are insignificant in one-month or three-month window either under OLS or fixed effects model. This study developed the financial information value relevance part of Amir and Lev (1996) to an emerging stock market and doubted the generalizing ability of their findings to Chinese high-technology industry.